Munc13-4 Is a Rab11-binding Protein That Regulates Rab11-positive Vesicle Trafficking and Docking at the Plasma Membrane - Johnson, Jennifer L. (J Biol Chem, 2016)
The small GTPase Rab11 and its effectors control trafficking of recycling endosomes, receptor replenishment and the up-regulation of adhesion and adaptor molecules at the plasma membrane. Despite recent advances in the understanding of Rab11-regulated mechanisms, the final steps mediating docking and fusion of Rab11-positive vesicles at the plasma membrane are not fully understood. Munc13-4 is a docking factor proposed to regulate fusion through interactions with SNAREs. In hematopoietic cells, including neutrophils, Munc13-4 regulates exocytosis in a Rab27a-dependent manner, but its possible regulation of other GTPases has not been explored in detail. Here, we show that Munc13-4 binds to Rab11 and regulates the trafficking of Rab11-containing vesicles. Using a novel Time-resolved Fluorescence Resonance Energy Transfer (TR-FRET) assay, we demonstrate that Munc13-4 binds to Rab11a but not to dominant negative Rab11a. Immunoprecipitation analysis confirmed the specificity of the interaction between Munc13-4 and Rab11, and super-resolution microscopy studies support the interaction of endogenous Munc13-4 with Rab11 at the single molecule level in neutrophils. Vesicular dynamic analysis shows the common spatio-temporal distribution of Munc13-4 and Rab11, while expression of a calcium binding-deficient mutant of Munc13-4 significantly affected Rab11 trafficking. Munc13-4-deficient neutrophils showed normal endocytosis, but the trafficking, up-regulation, and retention of Rab11-positive vesicles at the plasma membrane was significantly impaired. This correlated with deficient NADPH oxidase activation at the plasma membrane in response to Rab11 interference. Our data demonstrate that Munc13-4 is a Rab11-binding partner that regulates the final steps of Rab11-positive vesicle docking at the plasma membrane.